The interactive effect of maltreatment in the family and unstable institutional caregiving in predicting behavior problems in toddlers - Baptista, J.; Belsky, J.; Marques, S.; Silva, J. R.; Oliveira, P.; Mesquita, A.; Martins, C.; Soares, I. (Child Abuse and Neglect, 2014)
tThe current study extends research on the effects of institutionalization, most notably byexamining whether—and how—both pre-institutional maltreatment in the family and thestability and consistency of institutional care interact to shape emotional and behavioraldevelopment. Fifty Portuguese children, placed in residential institutions when 8 days to 26months of age, were evaluated using the Child Behavior Checklist when aged 18–31 months.Caregiver-rated internalizing and externalizing behavior problems proved to be unrelatedto both early family and institutional experiences, as main effects, but the interaction ofthese factors significantly predicted externalizing problems: a history of maltreatment inthe family coupled with unstable institutional caregiving arrangements predicted espe-cially elevated levels of externalizing problems. Results are discussed in terms of theimportance of more distal and proximate developmental experiences.